2008
DOI: 10.1136/bmj.a114
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ attitudes to the summary care record and HealthSpace: qualitative study

Abstract: Objective To document the views of patients and the public towards the summary care record (SCR, a centrally stored medical record drawn from the general practice record) and HealthSpace (a personal health organiser accessible through the internet from which people can view their SCR), with a particular focus on those with low health literacy, potentially stigmatising conditions, or difficulties accessing health care. Design 103 semistructured individual interviews and seven focus groups. Setting Three early a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
173
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(178 citation statements)
references
References 15 publications
2
173
0
Order By: Relevance
“…However, Lower levels of mental health, along with higher perceptions of general health, were positively correlated with levels of Internet use in Bowen et al [26]. Contrary to expectations, Greenhalgh et al [21] found that those defined as having a potentially stigmatising condition e.g. epilepsy, believed that the potential benefit of having an accessible health record in the event of a seizure outweighed the risk of a third party obtaining unauthorised access to their health record..…”
Section: Published As: Hardiker Nr Grant Mj Factors That Influence mentioning
confidence: 63%
See 2 more Smart Citations
“…However, Lower levels of mental health, along with higher perceptions of general health, were positively correlated with levels of Internet use in Bowen et al [26]. Contrary to expectations, Greenhalgh et al [21] found that those defined as having a potentially stigmatising condition e.g. epilepsy, believed that the potential benefit of having an accessible health record in the event of a seizure outweighed the risk of a third party obtaining unauthorised access to their health record..…”
Section: Published As: Hardiker Nr Grant Mj Factors That Influence mentioning
confidence: 63%
“…Openness to using eHealth resources was also highlighted as a facilitating factor in Flynn et al's study of Internet health information seeking [17]. Finally, Greenhalgh et al [21] noted that level of engagement and level of health literacy were associated with a positive response to eHealth services, while a lack of interest in one's own health was likely to reduce use. While prior use and a familiarity with the Internet appear to be significant factors affecting uptake of eHealth services, poor computer skills, not being able to find specific resources or not knowing that relevant resources are available also inhibit use.…”
Section: Published As: Hardiker Nr Grant Mj Factors That Influence mentioning
confidence: 99%
See 1 more Smart Citation
“…through electronic health records) 13,14 without explaining how benefits will result. Indeed, more critical approaches find potential for increased discrimination and inequality, 15 as digital inequalities are intertwined with other inequalities, such as poverty and remoteness, and parallel the uneven distribution of chronic disease. [16][17][18] Furthermore, some assume that all consumers are abandoning traditional media channels 14 and that the Internet enables 'unfettered access' to information for all.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is difficult to opt out if you are not aware of the implementation of the system. This model of consent has been criticised by the BMA [16,17] and was the subject of an independent evaluation by University College London, which concluded 'The "implied consent" model for creating and accessing a person's SCR should be revisited, perhaps in favour of 'consent to view' at the point of access' [18]. For example, consider having such conversations or discussions in the doctor's office.…”
Section: A Topical Area Involving Confidentiality -Summary Care Recormentioning
confidence: 99%